2015
DOI: 10.1371/journal.pone.0139715
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Toll-Like Receptor 9 Activation Promotes Systemic and Cardiac Inflammation, and Aggravates Diastolic Heart Failure in SERCA2a KO Mice

Abstract: AimCardiac inflammation is important in the pathogenesis of heart failure. However, the consequence of systemic inflammation on concomitant established heart failure, and in particular diastolic heart failure, is less explored. Here we investigated the impact of systemic inflammation, caused by sustained Toll-like receptor 9 activation, on established diastolic heart failure.Methods and ResultsDiastolic heart failure was established in 8–10 week old cardiomyocyte specific, inducible SERCA2a knock out (i.e., SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This, in turn, results in the release of large amounts of various pro-inflammatory cytokines and chemokines. In the animal model of experimentally induced left ventricular diastolic dysfunction, it was confirmed that the degree of diastolic dysfunction was associated with the degree of myocardial inflammation, of the intensity of pro-inflammatory cytokines expression and of myocardial infiltration by monocytes/macrophages [48]. The animal model used in this experiment does not allow the effects caused by direct TLR9 stimulation to be fully differentiated from the effects resulting from systemic inflammation.…”
Section: Toll-like Receptors and Inflammation In Hfmentioning
confidence: 77%
See 2 more Smart Citations
“…This, in turn, results in the release of large amounts of various pro-inflammatory cytokines and chemokines. In the animal model of experimentally induced left ventricular diastolic dysfunction, it was confirmed that the degree of diastolic dysfunction was associated with the degree of myocardial inflammation, of the intensity of pro-inflammatory cytokines expression and of myocardial infiltration by monocytes/macrophages [48]. The animal model used in this experiment does not allow the effects caused by direct TLR9 stimulation to be fully differentiated from the effects resulting from systemic inflammation.…”
Section: Toll-like Receptors and Inflammation In Hfmentioning
confidence: 77%
“…In the animal model of diastolic HF, it was confirmed, furthermore, that persistent activation of toll-like receptor 9 (TLR9) induces systemic and cardiac inflammatory response and increases diastolic dysfunction of the heart [48]. It is now believed that stimulation of both cardiac and non-cardiac TLR9 leads to the activation of NF-kB and interferon regulatory factor 3/7 (IRF 3/7).…”
Section: Toll-like Receptors and Inflammation In Hfmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the cardiac myocyte SERCA2a KO model does not adequately represent the molecular basis for, or the clinical features of, diastolic HF." [214] Item 18. Generalisability/translation Comment on whether, and how, the findings of this study are likely to generalise to other species or experimental conditions, including any relevance to human biology (where appropriate).…”
Section: Explanationmentioning
confidence: 99%
“…Further evidence for the key role of SERCA2a in HFpEF is as follows: (1) cardiomyocyte-specific deletion of SERCA2a in mice (SERCA2a KO) caused diastolic HF94; and (2) SERCA2a gene therapy could reverse ageing-induced diastolic dysfunction7 and endothelial dysfunction,95 which are HFpEF-related risk factors. Therefore, it is possible that impaired SERCA2a function in HFpEF contributes to incomplete relaxation and is associated with other mechanisms, including endothelial dysfunction, inflammation and interstitial fibrosis.…”
Section: Serca2a As a Potential Target In Hfpef With Low Bnp Levelsmentioning
confidence: 99%